Pendidikan Islam dalam Daya Juang Timnas Sepakbola Indonesia U-22 Meraih Juara SEA Games 2023 (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
This research focuses on the goals of Islamic education on the fighting power of the U-22 Indonesian football national team to win the 2023 SEA Games. This article is the result of findings from a qualitative type of literature research, using the Adversity Quotient theory approach. The data collection is litere in nature, then analyzed inductively. The results showed that the fighting power of the U-22 Indonesian Football National Team to win the 2023 SEA Games contained Islamic education, where a Muslim must cultivate a passionate passion in every soul to be able to achieve the expectations of the world and the hereafter. If you can't grab something from the world today, then there is still tomorrow to grab it. Implications of research on the need for a balance of fighting power between world affairs and the hereafter. The two cannot beat each other. Research is useful for developing the spirit of Islamic education.